The effects of prenatal stocking densities on the fear responses and sociality of goat (Capra hircus) kids. - Rachel M Chojnacki; Judit Vas; Inger Lise Andersen (PLoS ONE, 2014)
Prenatal stress (stress experienced by a pregnant mother) and its effects on offspring have been comprehensively studied but relatively little research has been done on how prenatal social stress affects farm animals such as goats. Here, we use the operational description of 'stress' as "physical or perceived threats to homeostasis." The aim of this study was to investigate the prenatal effects of different herd densities on the fear responses and sociality of goat kids. Pregnant Norwegian dairy goats were exposed to high, medium or low prenatal animal density treatments throughout gestation (1.0, 2.0 or 3.0 m2 per animal, respectively). One kid per litter was subjected to two behavioral tests at 5 weeks of age. The 'social test' was applied to assess the fear responses, sociality and social recognition skills when presented with a familiar and unfamiliar kid and the 'separation test' assessed the behavioral coping skills when isolated. The results indicate goat kids from the highest prenatal density of 1.0 m2 were more fearful than the kids from the lower prenatal densities (i.e. made more escape attempts (separation test: P < 0.001) and vocalizations (social test: P < 0.001; separation test: P < 0.001). This effect was more pronounced in females than males in the high density (vocalizations; social test: P < 0.001; separation test: P  =  0.001) and females were generally more social than males. However, goat kids did not differentiate between a familiar and an unfamiliar kid at 5 weeks of age and sociality was not affected by the prenatal density treatment. We conclude that high animal densities during pregnancy in goats produce offspring that have a higher level of fear, particularly in females. Behavioral changes in offspring that occur as an effect of prenatal stress are of high importance as many of the females are recruited to the breeding stock of dairy goats.